1992
DOI: 10.1073/pnas.89.24.12117
|View full text |Cite
|
Sign up to set email alerts
|

Empty and peptide-containing conformers of class I major histocompatibility complex molecules expressed in Drosophila melanogaster cells.

Abstract: Transfected DrosophUa melanogaster cellscan express large quantities of class I major histocompatibility complex molecules. Such molecules lack endogenous peptides because the Drosophila cells are devoid ofproteins necessary for intracellular peptide loading. The empty molecules are efficiently expressed on the cell surface and can acquire extracellular peptides. The conformation and stability ofempty murine class I molecules are determined by the source of P2-microglobulin. All ,2-microglobulin-induced confor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(93 citation statements)
references
References 27 publications
4
89
0
Order By: Relevance
“…The presence of such empty MHC class II molecules on the surface of DC was unexpected, because previous work in B cells suggested that MHC class II molecules that do not acquire peptide are retained intracellularly and degraded (21,48). However, we note that empty class II MHC proteins are stable at physiological temperature (37,49), unlike empty class I MHC proteins (49)(50)(51), and that class II MHC proteins can be produced in an empty or functionally empty form in several insect and mammalian cell lines (19,52,53). Thus, the intracellular retention of empty molecules observed in B cells may be caused by B-cell-specific mechanism rather than an intrinsic instability of empty class II MHC proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of such empty MHC class II molecules on the surface of DC was unexpected, because previous work in B cells suggested that MHC class II molecules that do not acquire peptide are retained intracellularly and degraded (21,48). However, we note that empty class II MHC proteins are stable at physiological temperature (37,49), unlike empty class I MHC proteins (49)(50)(51), and that class II MHC proteins can be produced in an empty or functionally empty form in several insect and mammalian cell lines (19,52,53). Thus, the intracellular retention of empty molecules observed in B cells may be caused by B-cell-specific mechanism rather than an intrinsic instability of empty class II MHC proteins.…”
Section: Discussionmentioning
confidence: 99%
“…All cDNAs were verified by sequencing. Three million SC2 cells (1 ϫ 10 6 /ml) in a well of a six-well plate were transfected with a total of 30 g of recombinant DNA and 1 g of the selection vector pNeofly (20) (a gift from L. Teyton) using a calcium phosphate transfection kit (Invitrogen, Carlsbad, CA). Stable transfectants were selected and maintained in 0.5 mg/ml G418 (Life Technologies).…”
Section: Expression Of Human Proteins In Drosophila Sc2 Cellsmentioning
confidence: 99%
“…The PCR product amplified by the second set of primers was fused with the sequence coding for 6× histidines and was subcloned into pRM-Ha for expression in Drosophila melanogaster cells (SC2) (41). The recombinant pRM-Ha, pRM-HB-EGF, was transfected into SC2 cells by phosphate methods.…”
Section: Figurementioning
confidence: 99%